1986
DOI: 10.1007/bf01262958
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neonatal pinealectomy on circadian periodicity of adrenocortical activity

Abstract: Newborn male and female rats aged between 24 and 48 hours were pinealectomized (Px) or sham-operated (Sh). Animals were sacrificed at 45 and 60 days of age, at the trough and peak of the adrenocortical diurnal cycle. Blood was collected for corticosterone determinations and the adrenal glands weighed. Adrenal gland weight was greater at 45 days (p less than 0.01) in Px rats than in Sh rats. This difference in adrenal gland weight disappeared in the group sacrificed 60 days post-operatively. On the other hand, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Regarding the effects of melatonin on glucorticoids, pinealectomy in Syrian hamsters does not affect the mean levels of cortisol, whatever the photoperiod. This confirms what is found by several studies in rats for corticoterone levels (Szafarczyk et al, 1983 ; Kaplanski and Ronen, 1986 ), albeit other investigations report increased levels of plasma corticosterone in pinealectomized rats (Oxenkrug et al, 1984 ; Alonso-Vale et al, 2004 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Regarding the effects of melatonin on glucorticoids, pinealectomy in Syrian hamsters does not affect the mean levels of cortisol, whatever the photoperiod. This confirms what is found by several studies in rats for corticoterone levels (Szafarczyk et al, 1983 ; Kaplanski and Ronen, 1986 ), albeit other investigations report increased levels of plasma corticosterone in pinealectomized rats (Oxenkrug et al, 1984 ; Alonso-Vale et al, 2004 ).…”
Section: Discussionsupporting
confidence: 86%
“…In terms of daily timing, a clear phase-advance is induced by pinealectomy in hamsters exposed to short days. Previous studies in adult rats found no effect of pinealectomy on the phase of corticosterone profile (Szafarczyk et al, 1983 ; Kaplanski and Ronen, 1986 ), while adrenal glands of rat fetus is entrained by maternal melatonin (Torres-Farfan et al, 2011 ). Furthermore, melatonin modulates in vitro molecular oscillations in the adrenal gland of adult monkeys (Valenzuela et al, 2008 ).…”
Section: Discussionmentioning
confidence: 91%
“…Neonate, adolescent, adult, and geriatric animals all display characteristic patterns of adrenocortical response to stimulation by ACTH (Allen and Kendall, 1967;Brett et al, 1986;Kaplanski and Ronen, 1986;Klemcke and Pond, 1991;Scaccianoce et al, 1990;Sonntag et al, 1987). (2) Sex of the animal.…”
Section: Introductionmentioning
confidence: 99%